Primary Spinal OPC Culture System from Adult Zebrafish to Study Oligodendrocyte Differentiation In Vitro - Kroehne, Volker; Tsata, Vasiliki; Marrone, Lara; Froeb, Claudia; Reinhardt, Susanne; Gompf, Anne; Dahl, Andreas; Sterneckert, Jared; Reimer, Michell M. (Frontiers in Cellular Neuroscience, 2017)
Endogenous oligodendrocyte progenitor cells (OPCs) are a promising target to improve functional recovery after spinal cord injury (SCI) by remyelinating denuded, and therefore vulnerable, axons. Demyelination is the result of a primary insult and secondary injury, leading to conduction blocks and long-term degeneration of the axons, which subsequently can lead to the loss of their neuron. In response to SCI, dormant OPCs can be activated and subsequently start to proliferate and differentiate into mature myelinating oligodendrocytes (OLs). Therefore, researchers strive to control OPC responses, and utilize small molecule screening approaches in order to identify mechanisms of OPC activation, proliferation, migration and differentiation. In zebrafish, OPCs remyelinate axons of the optic tract after lysophosphatidylcholine (LPC)-induced demyelination back to full thickness myelin sheaths. In contrast to zebrafish, mammalian OPCs are highly vulnerable to excitotoxic stress, a cause of secondary injury, and remyelination remains insufficient. Generally, injury induced remyelination leads to shorter internodes and thinner myelin sheaths in mammals. In this study, we show that myelin sheaths are quantitatively lost early after a complete spinal transection injury, but are re-established within 14 days after lesion. We introduce a novel, easy-to-use, inexpensive and highly reproducible OPC culture system based on dormant spinal OPCs from adult zebrafish that enables in vitro analysis. Zebrafish OPCs are robust, can easily be purified with high viability and taken into cell culture. This method enables to examine why zebrafish OPCs remyelinate better than their mammalian counterparts, identify cell intrinsic responses, which could lead to pro-proliferating or pro-differentiating strategies, and to test small molecule approaches. In this methodology paper, we show efficient isolation of OPCs from adult zebrafish spinal cord and describe culture conditions that enable analysis up to 10 days in vitro. Finally, we demonstrate that zebrafish OPCs differentiate into Myelin Basic Protein (MBP)-expressing OLs when co-cultured with human motor neurons differentiated from induced pluripotent stem cells (iPSCs). This shows that the basic mechanisms of oligodendrocyte differentiation are conserved across species and that understanding the regulation of zebrafish OPCs can contribute to the development of new treatments to human diseases.